Exploring Studies on Cooperative Principle in English Language Teaching: A Literature Review - Edy Waloyo; Sri Lestari; Ira Mutiaraningrum (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
The zeitgeist of studying CP has attracted scholars, particularly in Indonesia, to scrutinize its application in the ELT context. Previous studies endeavor to approach CP in the ELT through examining classroom interaction and maxim violation and flouting. Yet, limited studies have been attempted to deeply delineate and unravel its implication to culture and the online learning environment. Tapping further into the application of CP in an online learning environment may paint a rosy picture of how people cooperate in an online environment to avoid misunderstanding. This study also suggests an analysis and comparison of CP in the different cultural backgrounds as a promising study especially in Indonesia with its abundant cultural diversity.